Primary oral malignant melanoma: Clinicopathological series of four cases - Ajay Kumar; Ruchi Bindal; Devi C Shetty; Harkanwal P Singh (Wolters Kluwer Medknow Publications, 2012)
Melanoma of the oral cavity is a rare malignant disease. On account of the presence at relatively obscure areas in the oral cavity, most of oral malignant melanomas are diagnosed at a late stage. Early diagnosis is essential for successful treatment and perhaps is the key factor in improving the prognosis of oral malignant melanoma. However, no large clinical series exist, and in fact, clinical cases are the sole key source of information. We hereby present a series of four cases of primary oral malignant melanoma of South-East Asian ethnic origin, with long-term, regular follow-up. The age of the patients ranged between 40 and 70 years, with equal sex predilection, and the gingiva was found to be the most common site of its occurrence. Based on clinical and histological parameters, all the cases were diagnosed as primary malignant melanoma, which were further confirmed by using immunohistochemical markers.